2017
DOI: 10.1111/jir.12379
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide, cross‐sectional survey on unusual sleep postures and sleep‐disordered breathing‐related symptoms in people with Down syndrome

Abstract: Our study shows that there is a close relationship between unusual sleep postures and SDB-RSs. We recommend that all people with DS with unusual sleep postures should be checked for the presence of SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Parental reports of uncommon or abnormal sleeping positions, such as sleeping bent forward at the waist in a sitting position, should raise suspicion of an underlying sleep disorder. 19 , 20 Clinical examination findings in OSA involve factors that may result in upper airway airflow limitation. Each patient should be evaluated for adenotonsillar hypertrophy, relative macroglossia, enlarged or swollen nasal turbinates, poor muscle tone, and elevated BMI.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Parental reports of uncommon or abnormal sleeping positions, such as sleeping bent forward at the waist in a sitting position, should raise suspicion of an underlying sleep disorder. 19 , 20 Clinical examination findings in OSA involve factors that may result in upper airway airflow limitation. Each patient should be evaluated for adenotonsillar hypertrophy, relative macroglossia, enlarged or swollen nasal turbinates, poor muscle tone, and elevated BMI.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Particularly, parents in Asian countries, where co‐sleeping is common, may know more about their child's sleep habits than do parents in Western countries (Kuroda et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This coincides with previous studies of children with DS with an unusual sleep posture, compared with control samples, who reported a higher number of changes in position during sleep, night waking and an increased sleep duration (Kuroda et al . ; Nisbet et al . ; Ono et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that unusual sleep postures (USPs), such as sitting and leaning forward, were frequently observed in patients with DS [ 14 ]. Positional therapies are known to be effective in obstructive sleep apnea (OSA) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%